Pengaruh Independensi Auditor, Pemahaman Good Governance dan Self Efficacy Terhadap Kinerja Auditor Pada KAP Bali - Kirana, Ida Bagus Widya; Bambang Suprasto, H. (E-Jurnal Akuntansi; Vol 27 No 3 (2019)DO - 10.24843/EJA.2019.v27.i03.p08, 2019)
This study aims to examine the effect of auditor independence, understanding good governance and self efficacy on auditor performance. This research was conducted at the Public Accountant Office in Bali in 2018. The number of samples taken was 69 auditors who were willing to participate in this study. The sample in this study was determined by purposive sampling method. Data is collected using survey methods. The data analysis technique used is the analysis of Multiple Linear Regression and Moderated Regression Analysis (MRA). This study successfully showed auditor independence and understanding of good governance had a positive effect on auditor performance. This study also shows that self efficacy has a positive effect on auditor performance. This shows that if an auditor who has independence, understanding good governance and high self efficacy will affect his performance. Keywords : Auditor independence, understanding of good governance, self efficacy, auditor performance